Effects of Sodium Lactate Infusion in Two Girls with Glucose Transporter 1 Deficiency Syndrome - van Gemert, Loes A.; van Alfen, Nens; van Gaal, Lizzy; Wortmann, Saskia; Willemsen, Michèl A. (Neuropediatrics, 2023)
Background Glucose is an important fuel for the brain. In glucose transporter 1 deficiency syndrome (GLUT1DS), the transport of glucose across the blood–brain barrier is limited. Most individuals with GLUT1DS present with developmental problems, epilepsy, and (paroxysmal) movement disorders, and respond favorably to the ketogenic diet. Similar to ketones, lactate is an alternative energy source for the brain. The aim of this study is to investigate whether intravenous infusion of sodium lactate in children with GLUT1DS has beneficial effects on their epilepsy.Methods We performed a proof of principle study with two subjects with GLUT1DS who were not on a ketogenic diet and suffered from absence epilepsy. After overnight fasting, sodium lactate (600 mmol/L) was infused during 120 minutes, under video electroencephalographic (EEG) recording and monitoring of serum lactate, glucose, electrolytes, and pH. Furthermore, the EEGs were compared with pre-/postprandial EEGs of both subjects, obtained shortly before the study.Results Fasting EEGs of both subjects showed frequent bilateral, frontocentral polyspike and wave complexes. In one subject, no more epileptic discharges were seen postprandially and after the start of lactate infusion. The EEG of the other subject did not change, neither postprandially nor after lactate infusion. Serum pH, lactate, and sodium changed temporarily during the study.Conclusion This study suggests that sodium lactate infusion is possible in individuals with GLUT1DS, and may have potential therapeutic effects. Cellular abnormalities, beyond neuronal energy failure, may contribute to the underlying disease mechanisms of GLUT1DS, explaining why not all individuals respond to the supplementation of alternative energy sources.
Keywords: glucose transporter 1 deficiency syndrome; sodium lactate infusion; epilepsy; electroencephalography; experimental therapy